Social representations of obstetricians and neonatologists about fetal and early neonatal death certificate in the city of São Paulo - Daniela Schoeps; Fernando Lefevre; Zilda Pereira Silva; Hillegonda Maria Dutilh Novaes; Priscila Ribeiro Raspantini; Márcia Furquim de Almeida (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: The insatisfactory completeness of the variables in the Death Certificate (DC) makes it difficult to obtain specific perinatal mortality indicators. OBJECTIVE: To assess the social representation of physicians about the perinatal DC. METHODS: Twenty-five physicians were interviewed in 15 hospitals in the city of São Paulo, in 2009. Qualitative analysis was performed with the Collective Subject Discourse technique. RESULTS: The DC is primarily considered according to its legal aspect. Physicians feel responsible for fulfilling the cause of death. The majority of them reported receiving help from other professionals to complete information on maternal characteristics and identification variables. There is lack of information on the mother's pre-natal conditions, which can make it difficult to identify the perinatal cause of death, mainly in the Unified Health System (SUS) hospitals. Some participants received specific DC training only when attending medical schools. CONCLUSIONS: The organization of medical work may affect the completion of the DC, especially in hospitals from SUS. Other professionals contributed to this task and their training can improve the quality of information.